PENGARUH PARTISIPASI ANGGARAN, KOMITMEN ORGANISASI DAN PREFERENSI RESIKO TERHADAP SENJANGAN ANGGARAN PADA SEKTOR PUBLIK - NOVRIANI SUSANTI (JURNAL AKUNTANSI DAN KEUANGAN, 2023)
This study aims to test empirically whether budgetary participation, organizational commitment and risk preferences have an effect on budgetary slack in the public sector. This type of research is comparative causal research. The sampling technique for this study was purposive sampling, which is the parties involved in the preparation, implementation and accountability of the budget at the Regional Apparatus Organization (OPD) in Indragiri Hilir Regency with a total sample of 97 respondents. The analysis technique used is multiple linear regression. The results of the analysis show that budgetary participation has no effect on budgetary slack in regional apparatus organizations of Indragiri Hilir regency, organizational commitment has an effect on budgetary slack on regional apparatus organizations of Indragiri Hilir regency and risk preference has an effect on budgetary slack on regional apparatus organizations of Indragiri Hilir regency.